Panoramic radiography for detection of bilateral carotid calcified atheroma: An unusual Case Report - Maximiliano Bravo-Valenzuela; Javiera Reyes-Velásquez; Salvador Valladares-Pérez (Universidad de Concepción., 2020)
Introduction: Atherosclerosis is a progressive inflammatory disease that can trigger serious medical consequences like acute myocardial infarction or stroke. Case Report: The purpose of this study is to report an unusual case of finding calcified atheromatous plaques in the carotid arteries bilaterally using a panoramic radiography (PR). A 75-year-old female with a morbid history, attends the Teaching Dental Clinic of the Pontifical Catholic University with complementary exams. PR showed well-defined radiopaque structures adjacent to C4. Using a Doppler ultrasound, the presence of calcified atheromas in the right and left carotid arteries were confirmed. The patient was informed of these findings and is currently under medical follow-up. Conclusion: PR is a useful complementary resource in the detection of atherosclerotic plaques of the upper carotid region.